Contribuições para o aplicativo APR: novos limites de suportabilidade, perturbações via medições e sistematização no processo da configuração da rede elétrica - Gondim, Isaque Nogueira (2012)
The refunding requests coupled with the standard ANEEL 360/2009, which has contributed to the standard 61/2004, are considered the main Brazilian guidelines to cope with the subject of consumer reimbursement due to electrical appliances damages. Indeed, the subject is growing in valuable due to its social relevance, the commercial relationship between suppliers and final users and the growing number of requests involving the focused matter. As a direct consequence of these concerns it can be recognizes a number of investigations carried out in order to provide means to achieve a consistent way of correlating causes and effects, classically known as causal nexus. Within this context arises this PhD thesis that is aimed at the improvement of an existing computational program to provide final reports about the consistence or not of system disturbances and equipment damages. The proposed research work here considered has three main contributions to the present state of the art. First of all, the thesis is intended at proposing new dielectric and thermal withstand curves to some commercial products. Secondly, a strategy to characterize electrical system abnormal conditions by site measurements to feed a data bank to be used by the software. And finally, through a data bank based in geographic information system (GIS), the establishment of a fast and reliable way of feeding the software with the consumer feeder information as far as its topology and parameters are concerned.